THE EFFECTIVENESS OF JIGSAW IN IMPROVING STUDENTS’ READING COMPREHENSION - Hoerunnisa Neneng; Didi Suherdi (Journal of English and Education, 2017)
This research aims at investigating the effectiveness of Jigsaw in teaching reading comprehension, and it also aimed to investigate the students’ responses toward the Jigsaw technique. An English teacher and 30 seventh graders were involved as participants in this research. The data were obtained through classroom observation, giving treatments, and questionnaires. The data obtained from pre-test and post-test were analyzed by using SPSS 20 and ANATES V4 for windows. The data analysis from the independent t-test showed that there was significant difference in the result of post-test means between the experimental and the control groups. It showed that the score of the experimental group (M=24) was higher than control group (M=19). Furthermore, based on the result of the dependent t-test showed that tobt was greater than tcrit (8.976 2.064) at the level of significance 0,05 indicating that the null hypothesis (H0) was rejected. It means that there was a significant difference between students’ pre-test and post-test of experimental group after the treatments. The results of the study revealed that Jigsaw could be applied effectively to teach reading comprehension. Students were eager to discuss the information included in the descriptive texts one to another. In addition, the study also showed that the majority of students showed their interest in learning reading comprehension through Jigsaw. The results of the research indicated that using Jigsaw to teach reading comprehension made students tend to be active during the teaching and learning process, and it improved their comprehension about the descriptive texts.